The Common Risk Factor Approach: a rational basis for promoting oral health - Sheiham A, Watt RG (Blackwell Synergy, 2000)
Conventional oral health education is not effective nor efficient. Many oral health programmes are developed and implemented in isolation from other health programmes. This often leads, at best to a duplication of effort, or worse, conflicting messages being delivered to the public. In addition, oral health programmes tend to concentrate on individual behaviour change and largely ignore the influence of socio-political factors as the key determinants of health.